PRODUCTION OF BIOETHANOL FROM DIFFERENT PLANT SOURCES - kuriakose, Telphy (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Bio fuels from various sources such as Jatrophacurcas, Pongamiapinnata, Azadirachtaindica, Madhucaindica etcare produced till now. Ethanol is made biologically from cellulosic biomass, and using substrates such as molasses,fruit pulps and peels etc. are well known. Since the need of bioethanol has been increasing, in this study we usedpeels of citrus, non-citrus fruits, Pseudo stem of banana as substrates, due to its cheaper, ecofriendly and wholeyear availability. A chemical pre-treatment process using acid hydrolysis was applied. The amount of carbohydrateand alcohol was determined before and after the pretreatment. Cellulose degrading bacteria isolated from themidgut of the earthworms was inoculated into the pretreated samples, fermenting the substrate for alcoholproduction. Ethanol production in culture samples was determined by spectroscopic method. Results indicate thatethanol can be made from fruit peel residue and that the acid hydrolysis was effective in removal of lignin, whichacts as physical barrier to cellulolytic enzymes and causes the release of 20%-30% more sugar.